2005
DOI: 10.2139/ssrn.743130
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Financial Institutions

Abstract: and NBER. This paper is the introduction to the NBER book of the same title to be published by the University of Chicago Press. This introduction, and the book, represents the authors' opinions, not necessarily those of the Board of Governors of the Federal Reserve System or the NBER. We thank Frank Diebold, Jan Krahnen, and especially Jim O'Brien for comments. The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The present research was carried out at the level of the Romanian banking system. At the same time, Stulz & Carey (2006) demonstrated that at the level of the banking system, as a result of a crisis, excessive risk exposure could manifest itself, all the more so as banks usually face a range of risks. Wider risks (lending rate, operational risk, market risk, etc.)…”
Section: Fig 2 -Scatterplot Source: Own Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The present research was carried out at the level of the Romanian banking system. At the same time, Stulz & Carey (2006) demonstrated that at the level of the banking system, as a result of a crisis, excessive risk exposure could manifest itself, all the more so as banks usually face a range of risks. Wider risks (lending rate, operational risk, market risk, etc.)…”
Section: Fig 2 -Scatterplot Source: Own Researchmentioning
confidence: 99%
“…At the level of the banking system, there may be excessive risk exposure because the banks usually face a wider range of risks (e.g., lending rate, operational risk, market risk, etc.) that are strongly interconnected with the activities of the business environment, clients, legal entities or individuals (Stulz & Carey, 2006).…”
Section: Introductionmentioning
confidence: 99%